Mechanism of systolic anterior motion of mitral valve and site of intraventricular pressure gradient in hypertrophic obstructive cardiomyopathy. Issue 3 (March 1983) - Nagata, S; Nimura, Y; Beppu, S; Park, Y D; Sakakibara, H
Abstract : The mechanism of systolic anterior motion of the mitral valve and the localisation of the intraventricular pressure gradient were determined in 15 cases of hypertrophic obstructive cardiomyopathy by the combined use of real time two dimensional echocardiography and intracardiac manometry. We arrived at the following conclusions. The systolic anterior motion of the mitral echo in the M-mode echocardiogram can be classified into two types, I and II, based on two dimensional echocardiographic findings. In type I, the echo sources of systolic anterior motion are the anteriorly shifted mitral chordae and, in part, the papillary muscles. The intraventricular pressure gradient occurs at the level of the tip of the papillary muscle. The suprapapillary part of the outflow tract and the inflow part show a low pressure, while the apical cavity shows a high pressure. In type II, the echo sources of systolic anterior motion are the anterior and posterior mitral leaflets which are oriented in such a way as to obstruct the outflow tract. The pressure gradient occurs at the level of the anterior and posterior mitral leaflets. The inflow tract and the outflow tract just below the mitral leaflets show a high pressure, in contrast to type I systolic anterior motion. The inappropriate and maloriented papillary muscles play an essential role in causing both types of systolic anterior motion and outflow obstruction. The direction of the axis of the papillary muscle is changed in late systole, moving its tip away from the interventricular septum, resulting in a simultaneous reduction in systolic anterior motion.